RETRACTED ARTICLE: Methyldopa versus labetalol or no medication for treatment of mild and moderate chronic hypertension during pregnancy: a randomized clinical trial - Mohamed Rezk; Mohamed Emarh; Alaa Masood; Ragab Dawood; Elsayed El-Shamy; Awni Gamal; Hassan Badr (Hypertension in Pregnancy, 2020)
We, the Editor and Publisher of Hypertension in Pregnancy, have retracted the following article: Mohamed Rezk, Mohamed Emarh, Alaa Masood, Ragab Dawood, Elsayed El-Shamy, Awni Gamal & Hassan Badr (2020) Methyldopa versus labetalol or no medication for treatment of mild and moderate chronic hypertension during pregnancy: a randomized clinical trial, Hypertension in Pregnancy, 39:4, 393-398, DOI: 10.1080/10641955.2020.1791902 Since publication, significant concerns have been raised about the integrity of the data and reported results in the article. Concerns were also raised about this study’s similarity to the following study, which was not cited: Salama M, Rezk M, Gaber W, Hamza H, et. al. (2019). Methyldopa versus nifedipine or no medication for treatment of chronic hypertension During pregnancy: A multicenter randomized clinical trial. Pregnancy Hypertension 2019:17:54-8. DOI: 10.1016/j.preghy.2019.05.009. When approached for an explanation, the authors have not responded to the concerns raised, and they have not provided their original data or sufficient supporting information to verify that the research and publication comply with the journal’s editorial policies. As verifying the validity of published work is core to the integrity of the scholarly record, we are therefore retracting the article, and have informed the authors. The authors do not agree with the retraction. We have been informed in our decision-making by our editorial policies and COPE guidelines. The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as ‘Retracted’.